ASEAN Possibilities to Address Loss and Damage from Climate Change: Lessons from ASEAN Agreement on Transboundary Haze Pollution - KAEWKKHUNOK, SUPPAWIT (Journal of Political and Social Agenda, 2023)
Climate change is a major challenge in international cooperation and one of the greatest threats to humanity. Under a global environmental regime that seeks to mitigate and adapt to climate change, the concept of loss and damage was born to address the failures of both concepts. As the international community faces debate in advancing the concept of loss and damage, this research attempts to shed light on the potential of regional cooperation frameworks in advancing the concept. The research applies qualitative methodology to accomplish robust and reliable outcomes. This research uses ASEAN as a case study on the possibility of managing the loss and damage from climate change through the framework of environmental regionalism and environmental governance. The findings show that the common face of the threats of climate change among ASEAN member states is highly demanding their seriousness in addressing them. Moreover, shared experiences and working structures to tackle transboundary haze are positive factors that may encourage ASEAN to better manage the losses and damages from climate change. Thus, this research argues that advancing the concept of loss and damage can occur at the regional level as well without having to wait for clarity on global advocacy.